Implementation of Web Services in Web-Based Applications to Support the Student Assessment System at SMP Indriasana Palembang - hendrik fery herdiyatmoko (SISFOTENIKA, 2022)
Web technologies are emerging as a favorite platform for delivering data and services. Web technology is used in the REST architectural style, where REST is a web-based client-server communication architecture. REST server provides data in the form of a URL to be accessed by the client in the form of JSON. In this paper, it will be explained about the creation of a web service in the Student Assessment System. Using RESTful technology to exchange data in JSON form via URI (Uniform Resource Identifier). Restful technology or commonly abbreviated as rest only uses four request methods from the http method, namely GET to retrieve data, POST to enter data, PUT to change data and DELETE to delete data. The purpose of this study is to explore web service design using the WSIL (Web Service Implementation Lifecycle) methodology which includes the stages of web service development starting from analysis, design, coding, testing and deployment. The results of this study using the Web Service Implementation Methodology (WSIM) system development method have been successfully carried out on the implementation of web services. With this method there is a new paradigm in software development methods in addition to other common methods.